Impact of statistical significance and sample size on conclusions in sports science research: An analysis on the example of the relative age effect - Keune, K. (The Sport Journal, 2023)
Purpose The null hypothesis significance test (NHST) is a commonly applied statistical method for detecting effects in science, despite it being repeatedly criticized. Detractors argue that by focusing exclusively on NHST results, scientists fail to consider descriptive results, potentially leading to misinformed policy makers. They also point out that the influence of sample size on statistical power is often overlooked. This paper investigates whether this critique holds true in sport science research by analyzing the conclusions in publications about the relative age effect (RAE) - an effect manifested in biased birth date patterns.